Work Facilities as A Moderating Variable of The Influence of Work Ethic Variables on Employee Performance - Putri Ayu Permata Dewi; Arifhan Ady Dj; Muhammad Prasha Silitonga; Tono Wartono; Darmun Darmun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study is a qualitative study with a descriptive approach, namely an approach that explores the main topics in this study using descriptive texts. The data used in this study is secondary data that the researcher obtained indirectly from scientific articles, books, scientific journals, and various other sources commonly used in research. The data used was analyzed using smart PLS 4.0 analysis tools. The result in this artcile show that toll road infrastructure development has several positive impacts, including accelerating the distribution of goods and services, strengthening the industrial and manufacturing sectors, improving the tourism sector, encouraging the growth of MSMEs and the regional economy, and so on. In addition to its positive impacts on economic growth, toll road infrastructure development also has several negative impacts, one of which is environmental pollution. To address this issue, every toll road infrastructure development should also protect the environment and adhere to a sustainable development system.